Endocan is markedly overexpressed in severe erectile dysfunction. (23rd October 2017) - Akarsu, M.; Atalay, H. A.; Canat, L.; Ozcan, M.; Arman, Y.; Aydın, S.; Cil, E.; Kutlu, O.; Tükek, T.
Summary: This study aimed to measure the serum endocan level of patients with erectile dysfunction (ED) and to investigate the possible association between this and vasculogenic severe ED. We performed a prospective analysis of 86 consecutive patients affected by ED. Patients were divided into severe ED (IIEF‐5 score < 7) and mild or moderate ED (IIEF‐5 score > 7). A strong negative correlation was found between serum endocan levels and peak systolic velocity ( p  < .001 and r  = −.665) in men with severe ED. Univariate logistic regression analysis demonstrated that tobacco consumption ( p  < .05), serum total 25‐hydroxyvitamin D ( p  < .01), serum endocan levels ( p  < .01), peak systolic velocity ( p  < .01), hypertension ( p  < .001), dyslipidaemia ( p  < .001), metabolic syndrome ( p  = .026) and a history of a cardiovascular event ( p  < .001) significantly increase the risk of severe ED. In the multivariate logistic regression model, we also found that age, hypertension, metabolic syndrome, cardiovascular events and higher serum endocan levels were independently associated with severe ED. Circulating endocan may be used in daily practice as a new marker that correlates with cardiovascular risks and the severity of ED disease.